2011
DOI: 10.1002/asia.201000875
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Allylic Substitution of Simple Alkenes

Abstract: This report describes a nickel-catalyzed allylic substitution process of simple alkenes whereby an important structural motif, a 1,4-diene, was prepared. A key for this success is the use of an appropriate Ni-phosphine complex and a stoichiometric amount of silyl triflate. Reactions of 1-alkyl-substituted alkenes consistently provided 1,1-disubstituted alkenes with high selectivity. Insight into the reaction mechanism as well as miscellaneous application of the developed catalytic process is also documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…[9] Compared to palladium, nickel catalysts can easily insert into unactivated aryl chlorides and allow them to participate in coupling reactions.Furthermore, alkylnickel species are known to undergo much slower bhydride elimination than the palladium counterparts,w hich can be advantageous to avoid such as tep in catalytic reactions. [10] Previously,n ickel catalysts were reported to facilitate Heck-type arylation, [11] allylation, [12] and benzylation [13] of olefins.I narecent preliminary study,anickel-catalyzed enantioselective Heck cyclization generated oxindoles with quaternary centers. [14] Although Ronchi and Lebedev et al first reported the first nickel-catalyzed reductive Heck-type reactions of aryl halides and reactive acrylates in the 1980s, [15] an asymmetric version has remained elusive until today.…”
mentioning
confidence: 99%
“…[9] Compared to palladium, nickel catalysts can easily insert into unactivated aryl chlorides and allow them to participate in coupling reactions.Furthermore, alkylnickel species are known to undergo much slower bhydride elimination than the palladium counterparts,w hich can be advantageous to avoid such as tep in catalytic reactions. [10] Previously,n ickel catalysts were reported to facilitate Heck-type arylation, [11] allylation, [12] and benzylation [13] of olefins.I narecent preliminary study,anickel-catalyzed enantioselective Heck cyclization generated oxindoles with quaternary centers. [14] Although Ronchi and Lebedev et al first reported the first nickel-catalyzed reductive Heck-type reactions of aryl halides and reactive acrylates in the 1980s, [15] an asymmetric version has remained elusive until today.…”
mentioning
confidence: 99%
“…The research data supporting this publication can be accessed at https://doi.org/10.17630/33380f7f-28cd-45b8-b55b-dd6b83651e89. The authors have cited additional references within the Supporting Information [50–157] …”
Section: Methodsmentioning
confidence: 99%
“…The benchmark reaction between styrene boronic acid (1) and c-Hex NHPI ester (2) to give the desired C(sp 2 )-C(sp 3 ) coupled product is shown in Table 1. The optimized reaction conditions required 1 mol% of 4CzIPN 8 and 2 mol% of Ph3N as an electron shuttle (vide infra) with the reaction complete in 1 h (entry 1). This represented an improvement on previous conditions, which used 1 mol% of an Ru-based photocatalyst, 10 mol% of an electron shuttle additive (PhNMe2), and required 3 h for similar yield.…”
Section: Accepted Manuscriptmentioning
confidence: 99%